2019
DOI: 10.1002/ijgo.12952
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender and partner communication: Theory of planned behavior predictors for condom use among urban youth in Zambia

Abstract: Objective: To understand how knowledge and perceptions of condoms and partner communication influence use of condoms in a high HIV prevalence setting and genderspecific differences. Methods:A cross-sectional study was conducted in Zambia from 2015 to 2016. The survey included questions on demographics, sexual behavior, contraceptive perceptions, and behaviors. We constructed multivariate regression models using the Theory of Planned Behavior to determine associations between knowledge, perceptions, and perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…In recent published studies, the TPB has been successfully used to explain willingness to use PrEP among GBMSM in general [27], transgender women sex workers [36] and heterosexual population [37]. Moreover, many published studies also used the TPB to explain sexual behaviors [38][39][40], and utilization of HIV testing [41] and antiretroviral therapy [42].…”
Section: Introductionmentioning
confidence: 99%
“…In recent published studies, the TPB has been successfully used to explain willingness to use PrEP among GBMSM in general [27], transgender women sex workers [36] and heterosexual population [37]. Moreover, many published studies also used the TPB to explain sexual behaviors [38][39][40], and utilization of HIV testing [41] and antiretroviral therapy [42].…”
Section: Introductionmentioning
confidence: 99%
“…This result was confirmed in previous studies. Chowdhuri et al [15] conducted a study to assess how knowledge and perceptions of condoms and partners' communication influence the use of condoms in a high HIV prevalence setting in Zambia. Their results showed that partners' communication was associated with over three times higher odds of condom use.…”
Section: Discussionmentioning
confidence: 99%
“…a behavior, significant affirmation of behavior by others (subjective norms), and a sense of having control over the behavior (perceived behavioral control) are effective in the appearance of a certain behavior [11][12][13][14]. Prevention of sexually transmitted diseases requires strong control over behaviors, which are under influence of people's attitudes, subjective norms, and their perception of having control over them [15][16][17][18].…”
mentioning
confidence: 99%
“…We selected these variables based on a review of previous theory of planned behavior as well as tobacco use-related work. These include [ 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 37 , 38 , 39 ]. The response variable is intention to quit smoking, which equals 1 if the respondent wants/intends to quit smoking and 0 otherwise.…”
Section: Datamentioning
confidence: 99%